2013
DOI: 10.3171/2013.8.jns13832
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dural detachment on long-term tumor control for meningiomas treated using Simpson Grade IV resection

Abstract: Object Meningiomas treated by subtotal or partial resection are associated with significantly shorter recurrence-free survival than those treated by gross-total resection. The Simpson grading system classifies incomplete resections into a single category, namely Simpson Grade IV, with wide variations in the volume and location of residual tumors, making it complicated to evaluate the achievement of surgical goals and predict the prognosis of these tumors. Authors of the present study investigated the factors r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In our study, tumor locating in skull base was confirmed as an independent risk factor for 3-year PFS in multivariate analysis. Fukushima et al reported that skull base location was independently associated with tumor recurrence in patients following Simpson Grade IV resection (41). Another study also validated the higher recurrence rate of skull base tumor in a Grade I-V cohort (42).…”
Section: Discussionmentioning
confidence: 85%
“…In our study, tumor locating in skull base was confirmed as an independent risk factor for 3-year PFS in multivariate analysis. Fukushima et al reported that skull base location was independently associated with tumor recurrence in patients following Simpson Grade IV resection (41). Another study also validated the higher recurrence rate of skull base tumor in a Grade I-V cohort (42).…”
Section: Discussionmentioning
confidence: 85%
“…However, mass removal and generous coagulation of the dural attachment are highly recommended even in Simpson grade IV resection, because dural detachment is important to prevent recurrence in cases of Simpson grade IV removal in patients with intracranial meningiomas. 12) …”
Section: Discussionmentioning
confidence: 99%
“…Fukushima et al examined a series of grade IV meningiomas and showed that a volume of residual tumor > 4 cm 3 predicted recurrence on univariate analysis. 19 Materi et al posed a similar question and used postoperative volumetric MRI to examine patients with Simpson grade IV resections. 20 The authors reported that residual volume > 5 cm 3 was associated with increased growth rate.…”
Section: Simpson Grade IVmentioning
confidence: 99%